A new critical approach to the history of Palestine
1 online resource.
Keywords: "This volume is the first in a series which, under the auspices of the Palestine History and Heritage Project, introduces methods and principles for developing a comprehensive treatment of the history and cultural heritage of Palestine, based on evidence from archaeological, written and oral sources, under consideration of the most recent historical, archaeological and anthropological methods, the goals of which are neither nationalistic, ethno-centric, nor culturally exclusive and are aimed at a history of all the peoples of and in Palestine. The population of Palestine before World War I was ancient and, if one allows for the recurrent immigration and emigration endemic to Palestine's geographic role as land bridge, Palestine has supported the indigenous nature of its population with a remarkable continuity since the Neolithic period. At the same time, Palestine's people never belonged to or developed any particular, singular, dominating ethnicity, but rather has always distinguished itself with a large variety of regions and peoples, supported by a considerable variety of language, culture and history. This volume explores this diverse history against the backdrop of twentieth century scholarly construction of the history of Palestine as a history of a Jewish homeland, with roots in an ancient, biblical Israel, and examines the implications of this ancient and recent history for archaeology and cultural heritage." --